A new species of pontoniine shrimp genus Philarius Holthuis, 1952 (Crustacea: Decapoda: Palaemonidae) from the Great Barrier Reef of Australia - Marin, Ivan (Zootaxa, 2012)
A new species of coral-associated pontoniine shrimp, Philarius condi sp. nov., is described from Lizard Island, the GreatBarrier Reef of Australia. The new species can be clearly separated from the congeners by long fingers of chelipeds, whichare equal to the length of palm, and its unique ecological niche—living at the base of branches of stout-branched acroporidcorals such as Acropora monticulosa and A. gemmifera strongly influenced by waves in high energy ecosystems of reef slopes.